Translation Peculiarities of Russian Phraseological Units into Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents a comprehensive theoretical analysis of the process of translating Russian phraseological units into the Uzbek language. Phraseology serves as an essential linguistic component that encapsulates the cultural, historical, and conceptual worldview of a speech community. Translating phraseological units is not merely a linguistic procedure but a complex intercultural task that requires profound knowledge of both source and target cultures. This study explores the nature of phraseological units in Russian and Uzbek, discusses their classification, semantic and cultural peculiarities, and offers insights into translation strategies that account for linguistic and cultural discrepancies. The theoretical exploration includes analysis of equivalent, descriptive, adaptive, and literal translation methods within the framework of comparative linguistics.